Getting the most out of publicly available T-DNA insertion lines - Ulker, B.; Peiter, E.; Dixon, D.; Moffat, Caroline; Capper, R.; Bouche, N.; Edwards, R.; Sanders, D.; Knight, H.; Knight, M. (Wiley, 2008)
In the course of several different projects, we came to realize that there is a significant amount of untappedpotential in the publicly available T-DNA insertion lines. In addition to the GABI-Kat lines, which were designedspecifically for activation tagging, lines from the SAIL and FLAGdb collections are also useful for this purpose.As well as the 35S promoter chosen for activation tagging in GABI-Kat lines, we found that the 1¢2¢ bidirectionalpromoter is capable of activating expression of flanking genomic sequences in both GABI-Kat and SAIL lines.Thus these lines have added potential for activation tagging. We also show that these lines are capable ofgenerating antisense transcripts and so have the potential to be used for suppression (loss/reduction offunction) studies. By virtue of weak terminator sequences in some T-DNA constructs, transcript read-throughfrom selectable markers is also possible, which again has the potential to be exploited in activation/suppression studies. Finally, we show that, by selecting and characterizing lines in which the T-DNA insertionsare present specifically within introns of a target gene, an allelic series of mutants with varying levels ofreduced expression can be generated, due to differences in efficiency of intron splicing. Taken together, ouranalyses demonstrate that there is a wealth of untapped potential within existing insertion lines for studies ongene function, and the effective exploitation of these resources is discussed.